1999
DOI: 10.1046/j.1524-4725.1999.07165.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Dye Laser Treatment of Warts: An Update

Abstract: Pulsed dye laser is an effective treatment option for recalcitrant warts with an excellent side effect profile. However, our response rates were not as high as those previously reported, and we feel that further studies would be useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
2
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 18 publications
(24 reference statements)
5
66
2
2
Order By: Relevance
“…Palmar and periungual warts are cleared more effectively than plantar warts. 60,61,65 The main side-effects of PDL include local pain (although generally not severe enough to warrant stopping treatment), haemorrhagic bullae, pigmentary change and scarring. PDL is well tolerated by children, with two large cohort studies reporting complete response in 48% of treated warts 66 and 75% of children with palmoplantar warts.…”
Section: 21c Silver Nitrate (Level Of Evidence 2à)mentioning
confidence: 99%
“…Palmar and periungual warts are cleared more effectively than plantar warts. 60,61,65 The main side-effects of PDL include local pain (although generally not severe enough to warrant stopping treatment), haemorrhagic bullae, pigmentary change and scarring. PDL is well tolerated by children, with two large cohort studies reporting complete response in 48% of treated warts 66 and 75% of children with palmoplantar warts.…”
Section: 21c Silver Nitrate (Level Of Evidence 2à)mentioning
confidence: 99%
“…Furthermore, we assessed the treatment efficacy on recalcitrant warts in this study, which have an expected lower cure rate than simple warts. Several uncontrolled studies have found PDL able to clear 48-93% of simple and/or recalcitrant warts at various locations, and two studies have reported of low cure rates at 0% and 6.5% of warts [5][6][7][8][9][10][11][12][13]15,17,18]. Cure rates observed in these non-randomized, non-controlled studies do not account for the spontaneous resolution of warts and the high risk of bias makes interpretation and validity of these outcomes uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Newer, non-destructive interventions such as the pulsed dye laser (PDL) and intense pulsed light (IPL) have been suggested for treatment of recalcitrant warts [5][6][7][8][9][10][11][12][13][14][15]. The mechanism of action is assumed to be selective destruction of superficially papillary capillaries of the wart as well as thermal injury of the heat-sensitive HPV [5].…”
Section: Introductionmentioning
confidence: 99%
“…The provider-administered treatments include topical treatments (cryotherapy, podophyllin resin, trichloroacetic acid, bichloroacetic acid, and external application and intraurethral instillation of bacillus Calmette-Guerin); excisional treatments (curettage, electrosurgery, scissors excision, , cryosurgery and laser therapy); or injectable treatments (interferon or 5-fluorouracil/epinephrine gel implant) [25][26][27][28][29][30][31][32][33].…”
Section: Laser Treatment Of Wartsmentioning
confidence: 99%
“…Results were not superior than the ordinary electrocautery which remove blindly the infected tissue as well and may sometimes lead to textural changes. Several investigators have demonstrated the efficacy of 585 nm pulsed dye laser in treating warts [57][58][59][60][61][62]. The mechanism of action may be a result of intense heating of dermal vessels with collateral damage of virally infected keratinocytes.…”
Section: Laser Treatment Of Wartsmentioning
confidence: 99%